Stabilizing mechanisms enable dioecious trees to maintain synchrony in spring budburst under climate warming - Wu, Zhaofei; Gong, Yufeng; Zohner, Constantin M.; Vitasse, Yann; Li, Mingwei; Nie, Yangjing; Buonaiuto, Daniel M.; Morellato, Leonor Patricia Cerdeira [UNESP]; Guo, Zhendong; Wang, Shuxin; Wang, Nan; Wang, Hongzhou; et al. (Wiley, 2025)
Climate change could reduce dioecious plant fitness if the phenology of males and females responds differently to temperature. However, the extent to which spring phenological responses to climate differ between sexes in wind-pollinated dioecious trees remains poorly understood. Here, we combined ground observations with climate-controlled experiments to investigate sexual differences in spring budburst in Ginkgo biloba, Fraxinus chinensis, and Eucommia ulmoides. In 96% of in situ cases, male trees initiated budburst earlier than females, on average by 3.0 ± 0.4 d. This disparity was more pronounced in warmer regions. The experiment indicated that background climate is a key predictor of sexual disparity in budburst, with the largest differences observed in twigs originating from regions with higher mean annual temperatures and precipitation. However, these disparities declined in areas where mean annual temperatures exceeded 17.1°C, indicating nonlinear trends. This pattern aligns with the warming treatments, where sexual disparities decreased under spring warming of 2-10°C. These results suggest that while sexual disparities can be larger in warmer climates, dioecious trees possess stabilizing mechanisms, including photoperiod and chilling requirements, to maintain synchrony under warming conditions. Our findings enhance understanding of sex-specific phenological responses to climate change, with important implications for future species conservation and ecosystem management.